2021
DOI: 10.3390/civileng2020016
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Method of Determining Torsional Stability of the Multi-Storey Reinforced Concrete Buildings

Abstract: This article proposes a simplified method for determining the elastic radius ratio of the multi-storey reinforced concrete building. The elastic radius ratio is the benchmark parameter of the buildings in determining torsional stability during an earthquake. When buildings are torsionally flexible, the torsional component of seismic response amplifies the overall response of the building. Because of the numbers of simplified assumptions such as the adoption of the single-storey model, much of the published art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Kohiyama & Yokoyama [35] showed that even the most basic assumptions could be further improved by expanding the theory of structural eccentricity and concluding that there is an overlooked phenomenon called the Q-Δ effect (Q represents lateral force), accounting for large displacements. De-la-Colina & Valdés-González [36] continue with this thought process by proposing a design procedure that would not require accidental torsion but an amplification of design parameters, and Khatiwada & Lumantarna [37] propose a simplified method for determining torsional stability. Some research deals with the occurrence of torsion in regular symmetric structures in the nonlinear range [38][39][40][41][42], all pointing to the importance of this occurrence in regular buildings and specific issues regarding the material in question -RC or steel.…”
Section: Introductionmentioning
confidence: 99%
“…Kohiyama & Yokoyama [35] showed that even the most basic assumptions could be further improved by expanding the theory of structural eccentricity and concluding that there is an overlooked phenomenon called the Q-Δ effect (Q represents lateral force), accounting for large displacements. De-la-Colina & Valdés-González [36] continue with this thought process by proposing a design procedure that would not require accidental torsion but an amplification of design parameters, and Khatiwada & Lumantarna [37] propose a simplified method for determining torsional stability. Some research deals with the occurrence of torsion in regular symmetric structures in the nonlinear range [38][39][40][41][42], all pointing to the importance of this occurrence in regular buildings and specific issues regarding the material in question -RC or steel.…”
Section: Introductionmentioning
confidence: 99%